Global Connectivity and the Duty to Distant Others : Land Grab Expansion in sub-Saharan Africa - Teddla, Fitsum Resome; Justus Liebig University Giessen (My University, 2019)
Those who are interested on the idea of global justice have been excessively preoccupied with the moral question why should affluent societies be concerned about poor societies? The consensus has been that affluent societies have duty of minimum assistance due to the failure of the poor and the capacity of the affluent to help. In contrast, Pogge argues for duty of justice due to the harms well-off societies impose on the poor. By adopting the concept of distant others act closer for examining the reasons why affluent societies harm the poor, this study calls the arguments for the failure of the poor into question in support of harm. To do so, an ideal type was constructed, based on contemporary global land grab expansion in Africa, to examine the reasons distant others act closer and to analyze the circumstances of global justice. Accordingly, the difference between the poor and the affluent can be attributed to the ability of the later to act closer to the former not only by designing, manipulating and imposing global order, but also by expanding abroad, accumulating resources and retaining value-additive production processes that localizes their motives and delocalize resources and livelihood spaces thereof. This work introduces harm as an exported risk from the affluent and internalized by the poor, hence it argues the poor are not failed rather made to fail. It debunks the idea of failure and capacity as duty triggering factor by offering the motive of the affluent to mitigate their own domestic risks as sources of moral duty. Finally, it proposes a moral duty of risk absorption that can be discharged by releasing retained value-additive production processes while expanding abroad.
Keywords: ddc:320